A concrete composite material and a preparation method thereof
By using special reinforcement agents in concrete, the problem of reduced fluidity and slump retention caused by reinforcement materials is solved, the flowability and curing strength of concrete is improved, the preparation process is simplified, and more stable materials are provided in the construction field. application.
Patent Information
- Application Number
- CN202411450831.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-17
AI Technical Summary
After adding reinforcement materials, concrete composites may lead to a decrease in fluidity and slump retention, resulting in increased construction difficulty and increased internal defects and pores of materials, thereby reducing strength.
Using a reinforcement with good dispersion, the reinforcement prepared by reacting polycarboxylic acid water reducing agent, reducing agent and specific chemical substances under specific conditions is added to the concrete to improve the initial flowability and slump retention of the concrete. , and the curing strength of the material is enhanced by stirring and pre-homogenization.
It effectively reduces pores and defects inside the concrete, improves the stability and working performance of the material, improves the flowability and curing strength, simplifies the preparation process, and ensures uniform components and stable quality.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a concrete composite material and a preparation method thereof. Background Art
[0002] Concrete is an indispensable building material in modern buildings. With the continuous development of modern building technology, the requirements for concrete materials are also increasing. In order to meet the needs of buildings in terms of mechanical properties, durability and building quality, concrete composite materials have gradually become an important development direction in the field of construction. As an important form of high-performance concrete, concrete composite materials are mainly composed of basic materials such as water, cement, sand, aggregate (stone), and a certain proportion of reinforcing materials and other admixtures (such as superplasticizers, retarders, etc.) to form a new type of building material. These materials are combined by physical or chemical methods to form a material system with new properties compared with traditional materials. Concrete composite materials have the advantages of high strength, high durability, and high workability, and are widely used in engineering construction such as buildings, roads, bridges, and tunnels. In the field of construction, concrete composite materials can be used to make infrastructure such as columns, walls, and floors; in the field of roads and bridges, they can be used to make structures such as bridge bearings, piers, and covers; in addition, concrete composite materials also show broad application prospects in aerospace, marine engineering and other fields.
[0003] However, concrete composite materials still do not solve the problem of decreased fluidity and collapse resistance caused by adding reinforcing materials to traditional concrete, which greatly increases the difficulty of construction of concrete composite materials. In addition, when the reinforcing material has poor compatibility with concrete, it may also lead to an increase in internal defects and pores in the concrete material, thereby causing a decrease in strength. These are all urgent problems that need to be solved in the existing technology. Summary of the invention
[0004] The object of the present invention is to provide a concrete composite material and a preparation method thereof, by preparing a reinforcing agent with good dispersibility and using it in the preparation process of concrete materials, thereby reducing the pores and defects inside the concrete material, preventing the adsorption of cement paste in the concrete material, thereby improving the initial fluidity and collapse resistance of the concrete material, and improving the curing strength of the concrete material.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A concrete composite material, comprising the following raw materials in parts by weight: 44-53 parts of cement, 12-20 parts of sand, 18-26 parts of gravel, 3-7 parts of glass fiber, 0.4-0.5 parts of polycarboxylate water reducer, 0.1-0.2 parts of reducing agent, and 0.01-0.03 parts of reinforcing agent;
[0007] A method for preparing a concrete composite material comprises the following steps:
[0008] Step 1: Weigh each raw material according to mass fraction;
[0009] Step 2: Add water to the polycarboxylate water reducer, the reducing agent and the reinforcing agent, stir and mix to obtain a water reducer mother solution;
[0010] Step 3: Mix gravel, sand and glass fiber and add them into a mixer for pre-homogenization to obtain prefabricated material;
[0011] Step 4: adding the water reducing agent mother solution obtained in the second step to the prefabricated material obtained in the fourth step, and adding cement to stir and mix to obtain a concrete composite material.
[0012] Furthermore, the temperature condition for mixing and stirring the water reducing agent mother solution in the second step is 10-40°C.
[0013] Furthermore, in the third step, the rotation speed of the mixer is 60-120 r / min.
[0014] Furthermore, the reducing agent is one of ferrous sulfate, sodium sulfite, and sodium formaldehyde sulfoxylate.
[0015] Furthermore, the specification of the stones is 5-20 mm.
[0016] Further, the reinforcing agent is prepared by the following steps:
[0017] Step 1: para-aminobenzenesulfonic acid, triethylamine and tetrahydrofuran were mixed in a three-necked flask, magnetic stirring was turned on, acryloyl chloride was added dropwise to the three-necked flask under ice-water bath conditions, and then reacted under ice-water bath conditions for 2-3 hours. After the reaction was completed, concentrated ammonia water was added to the three-necked flask, and the organic layer was separated by a separatory funnel, and then rotary evaporated to obtain intermediate 1;
[0018] The reaction process is as follows:
[0019]
[0020] Step 2: Mix the intermediate 1, 2,7-naphthalenediamine, imidazole hydrochloride and xylene in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 120-140°C for 4-6 hours. After the reaction is completed, perform column chromatography to obtain the intermediate 2;
[0021] The reaction process is as follows:
[0022]
[0023] Step 3: Mix the intermediate 2, dodecane bromide and tetrahydrofuran in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 80-90° C. for 3 hours. After the reaction is completed, rotary evaporation is performed to obtain the enhancer;
[0024] The reaction process is as follows:
[0025]
[0026] Furthermore, the amount ratio of p-aminobenzenesulfonic acid, triethylamine, tetrahydrofuran and acryloyl chloride used in step 1 is 0.1 mol: 0.06-0.08 mol: 80-100 mL: 0.08-0.1 mol.
[0027] Furthermore, the amount ratio of the intermediate 1, 2,7-naphthalenediamine, imidazole hydrochloride and xylene used in step 2 is 0.07 mol: 0.01 mol: 0.003-0.004 mol: 40-60 mL.
[0028] Furthermore, the amount ratio of the intermediate 2, bromododecane and tetrahydrofuran used in step 3 is 0.007 mol: 0.014-0.018 mol: 40-60 mL.
[0029] Beneficial effects of the present invention:
[0030] 1) The present invention uses cement, sand, gravel, polycarboxylic acid water-reducing agent, reducing agent and reinforcing agent as raw materials to prepare a concrete composite material; the present invention firstly stirs and mixes the polycarboxylic acid water-reducing agent, reducing agent and reinforcing agent in water to obtain a water-reducing mother liquid, then mixes the sand, gravel and glass fiber and adds them into a mixer for pre-homogenization to obtain a prefabricated material, and finally adds the water-reducing agent mother liquid into the prefabricated material and adds cement for stirring and mixing to obtain a concrete composite material; the preparation method of the concrete composite material of the present invention is simple, and the components are uniform and the quality is stable.
[0031] 2) The present invention uses p-aminobenzenesulfonic acid and acryloyl chloride as raw materials and triethylamine as an acid-binding agent, utilizes the amino group of p-aminobenzenesulfonic acid and the acyl chloride group of acryloyl chloride to undergo amidation reaction to obtain intermediate 1, then utilizes the double bond of intermediate 1 and the amino group of 2,7-naphthalenediamine to undergo Michael addition reaction under the catalytic action of imidazole hydrochloride to obtain intermediate 2, and finally causes the tertiary amine structure of intermediate 2 to react with dodecane bromide to undergo quaternary ammonium salt reaction to obtain a reinforcing agent; the reinforcing agent of the present invention has a large steric hindrance, and can effectively prevent the adsorption of cement paste in concrete materials when it acts, and can reduce the pores and defects inside the concrete, thereby improving the stability and working performance of the concrete materials; the four ends of the reinforcing agent all have sulfonic structures, which can be hydrolyzed to form anchoring groups, and adsorb Electrostatic repulsion is generated on the surface of cement particles, destroying the flocculation structure of cement paste, improving the dispersibility of cement paste in concrete, and thus improving the initial fluidity of concrete materials. In addition, the quaternary ammonium salt structure on both sides of the reinforcing agent has good hydrophilicity, and the alkyl group itself has hydrophobicity. This structure enables the reinforcing agent to be oriented in the cement interface, reducing the surface tension of the cement interface, so that it can be better dispersed in the concrete material, thereby improving the effect of the reinforcing agent. Moreover, the reinforcing agent of the present invention will not affect the effect of the polycarboxylate water-reducing agent, so the two can work together to better improve the water-reducing effect of the water-reducing agent, achieve better fluidity and pumpability, and enhance the stability and curing strength of the concrete composite material.
[0032] 3) The preparation method of the concrete composite material of the present invention is simple, the components are uniform, and the quality is stable. Due to the addition of the reinforcing agent, the pores and defects inside the concrete are reduced, the fluidity is improved, and the stability and curing strength of the prepared concrete composite material are greatly improved, which can be widely used in the construction field. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] An enhancer is prepared by the following steps:
[0036] Step 1: 0.1 mol of p-aminobenzenesulfonic acid, 0.06 mol of triethylamine and 80 mL of tetrahydrofuran were mixed in a container, and after stirring evenly, 0.08 mol of acryloyl chloride was added dropwise to the container under ice-water bath conditions, and then reacted for 2 h under ice-water bath conditions. After the reaction was completed, concentrated ammonia water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 1;
[0037] Step 2: 0.07 mol of intermediate 1, 0.01 mol of 2,7-naphthalenediamine, 0.003 mol of imidazole hydrochloride and 40 mL of xylene were mixed in a container, stirred evenly, and reacted at 120°C for 4 hours. After the reaction was completed, intermediate 2 was obtained by column chromatography;
[0038] Step 3: 0.007 mol of intermediate 2, 0.014 mol of bromododecane and 40 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 80° C. for 3 h. After the reaction was completed, an enhancer was obtained by rotary evaporation.
[0039] Example 2
[0040] An enhancer is prepared by the following steps:
[0041] Step 1: 0.1 mol of p-aminobenzenesulfonic acid, 0.07 mol of triethylamine, and 90 mL of tetrahydrofuran were mixed in a container, and after stirring evenly, 0.09 mol of acryloyl chloride was added dropwise to the container under ice-water bath conditions, and then reacted under ice-water bath conditions for 2.5 hours. After the reaction was completed, concentrated ammonia water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 1;
[0042] Step 2: 0.07 mol of intermediate 1, 0.01 mol of 2,7-naphthalenediamine, 0.0035 mol of imidazole hydrochloride and 50 mL of xylene were mixed in a container, stirred evenly, and reacted at 130°C for 5 h. After the reaction was completed, intermediate 2 was obtained by column chromatography;
[0043] Step 3: 0.007 mol of intermediate 2, 0.016 mol of bromododecane and 50 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 85° C. for 3 h. After the reaction was completed, an enhancer was obtained by rotary evaporation.
[0044] Example 3
[0045] An enhancer is prepared by the following steps:
[0046] Step 1: 0.1 mol of p-aminobenzenesulfonic acid, 0.08 mol of triethylamine and 100 mL of tetrahydrofuran were mixed in a container, and after stirring evenly, 0.1 mol of acryloyl chloride was added dropwise to the container under ice-water bath conditions, and then reacted for 3 hours under ice-water bath conditions. After the reaction was completed, concentrated ammonia water was added to the container, and the organic layer was separated and rotary evaporated to obtain intermediate 1;
[0047] Step 2: 0.07 mol of intermediate 1, 0.01 mol of 2,7-naphthalenediamine, 0.004 mol of imidazole hydrochloride and 60 mL of xylene were mixed in a container, stirred evenly, and reacted at 140°C for 6 hours. After the reaction was completed, intermediate 2 was obtained by column chromatography;
[0048] Step 3: 0.007 mol of intermediate 2, 0.02 mol of bromododecane and 40 mL of tetrahydrofuran were mixed in a container, stirred evenly, and reacted at 90° C. for 3 h. After the reaction was completed, an enhancer was obtained by rotary evaporation.
[0049] Example 4
[0050] A concrete composite material, comprising the following raw materials in parts by weight: 44 parts of cement, 12 parts of sand, 18 parts of gravel, 3 parts of glass fiber, 0.5 parts of polycarboxylate water reducer, 0.2 parts of reducing agent, and 0.03 parts of reinforcing agent obtained in Example 1;
[0051] A method for preparing a concrete composite material comprises the following steps:
[0052] Step 1: Weigh each raw material according to mass fraction;
[0053] Step 2: adding water to the polycarboxylate water reducer, the reducing agent, and the reinforcing agent obtained in Example 1 and stirring and mixing at a temperature of 10° C. to obtain a water reducer mother solution;
[0054] Step 3: Mix the gravel, sand and glass fiber and add them into the mixer for pre-homogenization at a speed of 60r / min to obtain prefabricated material;
[0055] Step 4: adding the water reducing agent mother solution obtained in the second step to the prefabricated material obtained in the fourth step, and adding cement to stir and mix to obtain a concrete composite material.
[0056] Furthermore, the stone size used in this embodiment is 5 mm.
[0057] Furthermore, the reducing agent used in this embodiment is ferrous sulfate.
[0058] Example 5
[0059] A concrete composite material, comprising the following raw materials in parts by weight: 44 parts of cement, 12 parts of sand, 18 parts of gravel, 3 parts of glass fiber, 0.5 parts of polycarboxylate water reducer, 0.2 parts of reducing agent, and 0.03 parts of reinforcing agent obtained in Example 2;
[0060] A method for preparing a concrete composite material comprises the following steps:
[0061] Step 1: Weigh each raw material according to mass fraction;
[0062] Step 2: adding water to the polycarboxylate water reducer, the reducing agent, and the reinforcing agent obtained in Example 2 and stirring and mixing at a temperature of 25° C. to obtain a water reducer mother solution;
[0063] Step 3: Mix the gravel, sand and glass fiber and add them into the mixer for pre-homogenization at a speed of 90r / min to obtain prefabricated material;
[0064] Step 4: Add the water reducing agent mother solution obtained in the second step to the prefabricated material obtained in the fourth step, and add cement to mix and obtain a concrete composite material.
[0065] Furthermore, the stone size used in this embodiment is 15 mm.
[0066] Furthermore, the reducing agent used in this embodiment is sodium sulfite.
[0067] Example 6
[0068] A concrete composite material, comprising the following raw materials in parts by weight: 53 parts of cement, 20 parts of sand, 26 parts of gravel, 7 parts of glass fiber, 0.4 parts of polycarboxylate water reducer, 0.1 parts of reducing agent, and 0.01 parts of reinforcing agent obtained in Example 3;
[0069] A method for preparing a concrete composite material comprises the following steps:
[0070] Step 1: Weigh each raw material according to mass fraction;
[0071] Step 2: adding water to the polycarboxylate water reducer, the reducing agent, and the reinforcing agent obtained in Example 3 and stirring and mixing at a temperature of 40° C. to obtain a water reducer mother solution;
[0072] Step 3: Mix the gravel, sand and glass fiber and add them into the mixer for pre-homogenization at a speed of 120r / min to obtain prefabricated material;
[0073] Step 4: Add the water reducing agent mother solution obtained in the second step to the prefabricated material obtained in the fourth step, and add cement to mix and obtain a concrete composite material.
[0074] Furthermore, the stone size used in this embodiment is 20 mm.
[0075] Furthermore, the reducing agent used in this embodiment is sodium formaldehyde sulfoxylate.
[0076] Comparative Example 1
[0077] The "enhancing agent obtained in Example 3" used in Example 6 was removed, and the remaining raw materials and preparation steps remained unchanged.
[0078] Comparative Example 2
[0079] This comparative example is a high ductility concrete sold by Xi'an Wuhe Civil Engineering New Materials Co., Ltd.
[0080] Referring to the national standard GB8076-2008, a concrete composite material obtained in Examples 4-6 and Comparative Example 1 and a high ductility concrete sold by Xi'an Wuhe Civil Engineering New Materials Co., Ltd. in Comparative Example 2 were tested for concrete slump performance and loss comparison. According to the method specified in GB / T50081-2019, a concrete composite material obtained in Examples 4-6 and Comparative Example 1 and a high ductility concrete sold by Xi'an Wuhe Civil Engineering New Materials Co., Ltd. in Comparative Example 2 were tested for 7d and 28d compressive strength, respectively. The test results are shown in Table 1:
[0081] Table 1
[0082]
[0083] It can be seen from Table 1 that a concrete composite material of the present invention is superior to commercially available high ductility concrete in initial fluidity, collapse retention and cured strength, while the concrete composite material in Comparative Example 2 in which the reinforcing agent of the present invention is not added is not much different from the commercially available high ductility concrete in fluidity, but the collapse retention is not as good as the commercially available high ductility concrete. In summary, it is shown that the addition of the reinforcing agent of the present invention can effectively improve the initial fluidity and collapse retention of concrete, and also improve the strength after curing, so it can be widely used in the construction field.
[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A concrete composite material, characterized in that: Contains the following raw materials: cement, sand, gravel, glass fiber, polycarboxylate water reducer, reducing agent, reinforcing agent; Wherein, the reinforcing agent is prepared by the following steps: Step 1: p-aminobenzenesulfonic acid, triethylamine and tetrahydrofuran are mixed in a container, stirred evenly, and then acryloyl chloride is added dropwise to the container under ice-water bath conditions, and then reacted under ice-water bath conditions for 2-3 hours to obtain intermediate 1; Step 2: Mix the intermediate 1, 2,7-naphthalenediamine, imidazole hydrochloride and xylene in a container, stir evenly, and react at a temperature of 120-140° C. for 4-6 hours to obtain the intermediate 2; Step 3: The intermediate 2, dodecane bromide and tetrahydrofuran are mixed in a container, stirred evenly, and reacted at a temperature of 80-90° C. for 3 h to obtain the enhancer.
2. A concrete composite material according to claim 1, characterized in that: The amount ratio of p-aminobenzenesulfonic acid, triethylamine, tetrahydrofuran and acryloyl chloride used in step 1 is 0.1 mol: 0.06-0.08 mol: 80-100 mL: 0.08-0.1 mol.
3. The concrete composite material according to claim 1, characterized in that: The amount ratio of the intermediate 1, 2,7-naphthalenediamine, imidazole hydrochloride and xylene used in step 2 is 0.07 mol: 0.01 mol: 0.003-0.004 mol: 40-60 mL.
4. The concrete composite material according to claim 1, characterized in that: The amount ratio of intermediate 2, bromododecane and tetrahydrofuran used in step 3 is 0.007 mol: 0.014-0.016 mol: 40-60 mL.
5. A method for preparing a concrete composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Weigh each raw material according to mass fraction; Step 2: Add water to the polycarboxylate water reducer, the reducing agent and the reinforcing agent, stir and mix to obtain a water reducer mother solution; Step 3: Mix gravel, sand and glass fiber and add them into a mixer for pre-homogenization to obtain prefabricated material; Step 4: adding the water reducing agent mother solution obtained in the second step to the prefabricated material obtained in the third step, and adding cement to stir and mix to obtain a concrete composite material.
6. The method for preparing a concrete composite material according to claim 5, characterized in that: In the second step, the temperature condition for mixing and stirring the water reducing agent mother solution is 10-40°C.
7. The method for preparing a concrete composite material according to claim 5, characterized in that: In the third step, the speed condition of the mixer is 60-120r / min.
8. The method for preparing a concrete composite material according to claim 5, characterized in that: The reducing agent is one of ferrous sulfate, sodium sulfite and sodium formaldehyde sulfoxylate.
9. The method for preparing a concrete composite material according to claim 5, characterized in that: The specification of the stone is 5-20mm.
10. The method for preparing a concrete composite material according to claim 5, characterized in that: The mass proportions of the raw materials used are: 44-53 parts of cement, 12-20 parts of sand, 18-26 parts of gravel, 3-7 parts of glass fiber, 0.4-0.5 parts of polycarboxylic acid water reducer, 0.1-0.2 parts of reducing agent, and 0.01-0.03 parts of reinforcing agent.
